Cover Feature: Evidence of Mixed‐Ligand Complexes in Cu−CHA by Reaction of Cu Nitrates with NO/NH3 at Low Temperature (ChemCatChem 16/2019). Issue 16 (28th August 2019) - Negri, Chiara; Borfecchia, Elisa; Cutini, Michele; Lomachenko, Kirill A.; Janssens, Ton V. W.; Berlier, Gloria; Bordiga, Silvia
Abstract : The Cover Feature depicts the chemistry taking place within the cages of the Cu‐exchanged chabazite zeolite, during the reaction of pre‐formed Cu II ‐nitrates with a NO/NH3 flow at 50 °C. In their Full Paper, Gloria Berlier and co‐workers investigate the low temperature reactivity of Cu‐CHA towards the main reactants of the NH3 ‐assisted Selective Catalytic Reduction, by in situ FTIR, Diffuse Reflectance UV‐Vis and XAS spectroscopies. Framework‐interacting Cu II ‐nitrates, formed by reaction with a diluted NO/O2 mixture, are readily transformed by interaction with NH3 (alone or in a NO/NH3 mixture) into mixed‐ligand mobile [Cu II (NH3 )3 (NO3 )] + complexes. DFT calculations indicate that the modification of the nitrate ligand configuration from chelating bidentate to monodentate during this transformation is favored by the NH3 solvation environment. More information can be found in the Full Paper by Chiara Negri et al. on page 3828 in Issue 16, 2019 (DOI: 10.1002/cctc.201900590 ).